O uso dos diferentes modelos de letras manuscritas em atividades de alfabetização : uma análise de cadernos utilizados entre as décadas de 1990 e 2010 - Rosa, Aliene Pinto da (2023)
This master's dissertation sought to find out which practices were related to the discourse on the psychogenesis of literacy between 1990s and 2010s. To this end, the research was carried out based on the analysis of school notebooks – the proposed activities and the handwritten letters that appeared during this period. The question that guides this project is: what exercises were proposed by the teachers and what were the models of handwritten letters, in the literacy process between the 1990s and 2010s, based on the analysis of literacy notebooks? The objective of this research was to carry out a survey of the types of activities proposed by teachers, between the 1990s and 2010s, and what were the models of handwritten letters used in the literacy process, having as a parameter 5 (five) years after the book Psychogenesis of the Written Language. Regarding the methodology of this investigation - which is part of a qualitative approach seeking to visualize the aspects that affected and influenced the use of cursive in the literacy process - this is a documentary research, as literacy notebooks were used, from the city of Pelotas, in the state of Rio Grande do Sul, all in the period involving the literacy process (1st year or 1st grade of Elementary School and 2nd year or 2nd grade of Elementary School), from public and private schools, between 1990s and 2010. 28 notebooks from HISALES were used, randomly chosen, as follows: 11 notebooks from the 1990s, 10 notebooks from the 2000s and 7 notebooks from the 2010s. To analyze the notebooks, which were the research objects of this dissertation, I followed some pre-stipulated steps, which are described in the Methodology Item. As a result of this investigation, after analyzing the literacy notebooks, it was evident that between the decades researched – from 1990 to 2010 – marked and significant changes were perceived in the activities and practices recorded in the notebooks, which reflected in the way of teaching literacy on the part of teachers and, also, it was noticed that there was the permanence of some models of activities, which were registered in the notebooks, in all the analyzed decades.